SOCIAL FRAMEWORK AND CHARACTERISTICS OF DAILY NEWSPAPER MARKET’S FUNCTIONING IN SERBIA - Penezić, Slobodan M (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Article sublimates a part of the research directed towards the current moment in the world of media, that is shaped by the influences of various challenges, which lead to the appearance of the so-called global media crises. Analyzing this global context, we are examining the nature of the relationship between media editing and media business results. Starting from the question of the existence of interdependence of these two dimensions and its consequences, the actual goal is to examine what can be done regarding the organization of media work to create a positive impact on its business, but also vice versa − how business results affect media work. In accordance with the situation, especially unfavorable for daily newspapers, this type of media was analyzed more directly, and as a sample we used Serbia in the period from 2008 to 2016; namely newspapers "Danas", "Politika" and "Kurir" − media system representative for such interpretation. We tried to gain insight and explain the work of the newspaper from a scientific point of view, and thus analyze the validity of certain global assumptions. The aim is to explain the challenges that the media face (external factors) and media responses to them (internal) as an interdependent process. With a focus on the internal, which has two aspects (professionalism of media actors), the goal is to formulate an optimal model of media work, primarily FOR those whose survival is most endangered, and therefore to indicate changes in their business philosophy. The general hypothesis, proven in research, indicates that the formation of a model for longer-term stability is conditioned by the predominance of the positive influence of media management over the negative influence of external factors.